Diet quality is associated with obesity and hypertension in Australian adults: a cross sectional study - Katherine M. Livingstone; Sarah A. McNaughton (BMC, 2016)
Abstract Background Poor diet, characterized by a low diet quality score, has been associated with greater prevelence of obesity and hypertension. However, the evidence is inconsistent across diet quality scores and by sex. The aim was to investigate the relationship between diet quality and obesity and hypertension. Methods Adults (n = 4908; age 45.2 ± 0.24 years) were included from the cross-sectional Australian Health Survey 2011-2013. Two 24-h dietary recalls were used to derive the dietary guideline index (DGI) and recommended food score (RFS). Logistic regression investigated relationships between diet quality score and odds ratio of obesity, hypertension and obesity-associated hypertension. Results In the highest tertile of DGI, but not RFS, individuals were less likely to be obese (men: OR 0.64, CI: 0.45, 0.92, P-trend = 0.014; women: 0.68, 0.48, 0.96, P-trend = 0.025) and to have central adiposity (men: 0.68, 0.48, 0.97, P-trend = 0.030; women: 0.53, 0.37, 0.77, P-trend = 0.001) compared with the lowest tertile. Men, but not women, in the highest tertile of DGI and RFS were less likely to be hypertensive (DGI: 0.56, 0.37, 0.85, P-trend = 0.006; RFS: 0.62, 0.41, 0.94, P-trend = 0.021) compared with the lowest tertile. In men with obesity, but not normal weight men or women, those in the highest tertile of DGI were less likely to be hypertensive (0.53, 0.36, 0.78, P-trend = 0.001) compared with the highest tertile. Conclusions Higher diet quality, as estimated using DGI, was associated with lower odds ratio of obesity in men and women. Odds ratio of hypertension was lower in men, but not women, with a high diet quality score compared with a low score, while obesity-associated hypertension was only associated with diet quality score in men with obesity. Longitudinal studies are needed to evaluate whether diet quality predicts risk of obesity and hypertension.